2017
DOI: 10.1017/s1041610216002246
|View full text |Cite
|
Sign up to set email alerts
|

Severe obesity increases the prevalence but not the incidence of depressive symptoms in the elderly-population-based cohort in Southern Brazil

Abstract: Severely obese individuals presented a similar incidence of depressive symptoms compared to those with normal BMI/WC, but higher prevalence. Intermediary values of body weight status decrease the risk of depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In another multicenter study, which included baseline data from 17 European countries, the percentage of obesity among depressed and non-depressed elderly people was 29% and 23%, respectively (p < 0.001) [15]. Furthermore, a large community-based study in Southern Brazil by Goes et al [26] reported that obese elderly people had higher prevalence of being depressed than those with normal weight (OR = 2.34). The relationship between body weight status and depression is multifactorial and seems to be influenced by biological, psychological, and behavior-related factors [27].…”
Section: Discussionmentioning
confidence: 97%
“…In another multicenter study, which included baseline data from 17 European countries, the percentage of obesity among depressed and non-depressed elderly people was 29% and 23%, respectively (p < 0.001) [15]. Furthermore, a large community-based study in Southern Brazil by Goes et al [26] reported that obese elderly people had higher prevalence of being depressed than those with normal weight (OR = 2.34). The relationship between body weight status and depression is multifactorial and seems to be influenced by biological, psychological, and behavior-related factors [27].…”
Section: Discussionmentioning
confidence: 97%
“…Further, while a larger proportion of older adults experience anxiety and depressive symptoms that seriously affect their quality of life, they are unwilling to seek treatment or do not meet psychiatric diagnostic criteria [ 6 ]. Across cultures and regions, the prevalence of depression among older adults ranges between 11.4–36.7% [ 7 – 9 ], while the incidence of anxiety is between 14.2–39.4% [ 10 12 ]. In China, previous regional surveys have shown that the prevalence of anxiety and depression among older adults ranges between 11.77–22.3% and 26.5–40.3%, respectively [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depression is characterized by loss of interest, fatigue, and feelings of worthlessness and guilt and was reported to be ranked first in the global disease burden in terms of disability-adjusted life years (DALYs) by 2030 (World Health Organization, 2012). The prevalence of depressive symptoms among the elderly is high: 23.3% in southern Brazil (Goes et al , 2017), 36.7% in Iran (Taheri Tanjanai et al , 2017), and 11.4% in India (Behera et al , 2016). Data drawn from the second wave of the China Health and Retirement Longitudinal Study (CHARLS) showed that more than 32.55% of the elderly in China had depression (Xu et al , 2016).…”
Section: Introductionmentioning
confidence: 99%